2014
DOI: 10.7314/apjcp.2014.15.3.1339
|View full text |Cite
|
Sign up to set email alerts
|

Mitochondrial DNA Levels in Blood and Tissue Samples from Breast Cancer Patients of Different Stages

Abstract: Aims: Alterations in mitochondrial DNA (mtDNA) have been implicated in carcinogenesis and tumor progression. We here evaluated the diagnostic and prognostic potential of mtDNA as a biomarker for breast cancer. Methods: Using multiplex real-time polymerase chain reaction, nuclear DNA (nDNA) and mtDNA levels in serum, buffy coat, tumor, and tumor-adjacent tissue samples from 50 breast cancer patients were determined and assessed for associations with clinicopathological features. To evaluate mtDNA as a biomarker… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
10
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 33 publications
1
10
0
Order By: Relevance
“…Similarly, the correlation between high mtDNA copy number and cancer prognosis was insignificant in the overall evaluation and showed relative large heterogeneity both in the overall survival and disease-free survival analyses. One previous study documented the considerable discrepancy between the mtDNA levels in peripheral blood and tumor tissue extracted from the same patients and suggested the moderate irrelevance of them44. Our results further expounded that low mtDNA copy number extracted from tumor tissue was strongly associated with poor survival but the result was opposite in the blood sample.…”
Section: Discussionsupporting
confidence: 72%
“…Similarly, the correlation between high mtDNA copy number and cancer prognosis was insignificant in the overall evaluation and showed relative large heterogeneity both in the overall survival and disease-free survival analyses. One previous study documented the considerable discrepancy between the mtDNA levels in peripheral blood and tumor tissue extracted from the same patients and suggested the moderate irrelevance of them44. Our results further expounded that low mtDNA copy number extracted from tumor tissue was strongly associated with poor survival but the result was opposite in the blood sample.…”
Section: Discussionsupporting
confidence: 72%
“…Increase in molecular and genetic studies relevant to carcinogenesis, which contributes to develop new screening, diagnosis and treatment methods, improves the course of cancer. (Xia et al 2014;Li et al 2015).…”
Section: Introductionmentioning
confidence: 99%
“…infarction (Wang et al, 2015), autism (Zhang et al, 2010a), hepatic transplantation (Hu et al, 2015) and hemodialysis (Eleftheriadis et al, 2014). Multiple studies have shown that mtDNA as a potential biomarker of different neoplastic conditions such as prostate cancer (Ellinger et al, 2008), germ cell cancer (Ellinger et al, 2009) and breast cancer (Xia et al, 2014…”
Section: Introductionmentioning
confidence: 99%